The Origin of the Eight-Year Generating Cycle - Moore, Henry Ludwell (Quarterly Journal of Economics, 1921)
The persistence of the eight-year generating cycle in England for one hundred and sixty years; the congruence of the eight-year crop cycles in England, France, and the United States; the persistence of the eight-year meteorological cycles, and their congruence in Europe and America; the congruence of the economic and meteorological cycles — these uniformities and agreements suggest that their cause must be sought in a cosmical cycle. The probable cause is the planet Venus in its eight-yearly periodic motion with respect to the Earth and the Sun. I. Economic cycles, 2. — II. Meteorological cycles, 8. — III. The cause of the eight-year generating cycle, 18.